Effects of Inorganic Acid Modification on Photocatalytic Performance of TiO2 and Its Activity‐Enhanced Mechanism Related to Adsorbed O2. Issue 2 (4th November 2013) - Cui, Haiqin; Cao, Yue; Jing, Liqiang; Luan, Yunbo; Li, Na
Abstract In this work, commercial P25 TiO2 is modulated by post‐treatments with different acidic substances, and the effects of residual acidic substances on the photogenerated charge separation of TiO2 and its photocatalytic activity are investigated in detail. It is demonstrated by means of atmosphere‐controlled surface photovoltage spectroscopy that an increase in acid surface modification is favorable for improving the photogenerated charge separation of TiO2. As a result, its photocatalytic activity for the degradation of gas‐phase acetaldehyde is enhanced greatly. On the basis of measurements of O2 temperature‐programmed desorption of untreated and treated TiO2, it is confirmed that an increased amount of acid surface modification promotes the adsorption of O2 on TiO2. Hence, it is suggested for the first time that an increase in surface acidity through post‐treatment with an appropriate amount of acidic substance leads to a clear enhancement of the photocatalytic activity of TiO2 by promoting O2 adsorption, and thus, improving the photogenerated charge separation of TiO2. This work provides a feasible route for the synthesis of high‐activity oxide‐based semiconductor photocatalysts through surface modification with stable inorganic acids.